Book Review: Roh Kudus, Doa, dan Kebangunan - Aritonang, Arthur (STAK Reformed Remnant Internasional, 2025)
This study aims to highlight the doctrine of the Spirit language and its practices in one of the Protestant church’s denominations. The Spirit language (Greek: Glossolalia) shown to the congregation is an obscure language, repeatedly spoken in the same words, disorderly, emphasizing the wild emotional side and it has long been believed by Christians to be a manifestation of the tongue. For ST understanding such a tongue does not fit the Bible as first, the church provides the absolute standard that the characteristic of a Christian having the Holy Spirit is to have the gift of speaking a tongue or spirit. Second, a person with a holy spirit can be seen from outward expressions such as falling back, unconscious, rolling on the ground, and praying all his body trembles. ST does not believe in the language of spirit, because in the Bible the disciples and Paul speak in the spirit language. But it is worth understanding that the gift of spirit speaking is one of the nine gifts of the Holy Spirit 1 Corinthians 12.